Modelagem hidrossedimentológica de grandes bacias com propagação inercial de vazão: estudo de caso da Bacia do Rio Madeira - Foeger, Lizandra Broseghini (2019)
Soil erosion is a complex environmental problem, responsible for soil modification and sediment transfer from its origin site. Technological progress has allowed the developing of computational models to help the understanding of these processes. In large scales, it is usual to use conceptual and distributed models that integrate a hydrological module in its structure also connected with a GIS environment. The MGB SED is a hydrossedimentological model coupled with the MGB model, developed to estimate the generation, transport and redistribution of sediments in large watersheds. However, the use of the hydrodynamic flood routing model is only available for the Amazon basin. The aim of this study was to perform the coupling of the MGB-SED model to the latest version of the MGB model, which uses the inertial flood routing method, and to apply the model to the Madeira River basin for comparison with the results of the hydrodynamic model. The evaluated sediment characteristics was the erosion in river stretches, estimated annual suspended sediment load, suspended sediment transport and seasonal variability of suspended sediment. The coupling of MGB-SED generated reasonable results, similar with the simulation that uses the hydrodynamic flood routing, reaffirming the hydrological and sedimentological behavior in the Madeira River basin previously estimated with the hydrodynamic MGB version. For most stations, both fluviometrics and sedimentometrics, the statistical values calculated to evaluate the simulation performance with the inertial model and the hydrodynamic model were quite similar. The easier preparation of data for the inertial model, as well as its computational simplicity, when compared to the hydrodynamic model, can be considered advantages of the new coupled model, which also made the model applicable to any basin, without losses to the representation of local hydrosedimentological dynamics.